Simulate the aerodynamic olfactory effects of gas-sensitive UAVs: A numerical model and its parallel implementation. (December 2016) - Luo, Bing; Meng, Qing-Hao; Wang, Jia-Ying; Ma, Shu-Gen
Highlights: This model is an interdisciplinary approach that integrates free vortex methods and statistical approaches. Both induced velocity field and gas dispersion calculation processes are described. Parallel implementation for real-time simulation of the model is described. 3D Kernel DM+V/W algorithm is tested for 3D gas distribution mapping with a UAV using this model. Abstract: The attempts of robot implementations and simulation framework designs for the solution to three dimensional (3D) robot active olfaction problems are reviewed. A numerical model is proposed for real-time simulations of the gas dispersion under the air flow disturbance introduced by the rotating propellers of gas-sensitive unmanned aerial vehicles (UAVs). The model is an interdisciplinary approach that integrates free vortex methods and statistical approaches. Both induced velocity field and gas dispersion calculation processes are described. Parallel implementation of the model is also discussed. Challenging examples of the application of the model to the simulation of 3D robot active olfaction problems are shown, including a gas distribution mapping test. Theoretically the model is suitable for the real-time simulation of any type of gas-sensitive UAVs which gain thrust with propellers.